JADID PRESS AS A COMMUNICATIVE PLATFORM OF TURKESTAN MODERNIZATION (Web of Teachers: Inderscience Research, 2026)
This article analyzes the role of the Jadid press in the process of modernization, which was formed in Turkestan at the beginning of the 20th century, as a communicative platform. The study was carried out on the basis of publications such as "Taraqqiy", "Oyina", "Sadoi Turkistan", "Hurriyat" and "Taraqqiy", "Oyina", "Sadoi Turkestan", "Hurriyat" and "Taraqqiy", "Oyina", "Sadoi Turkestan", "Hurriyat". Through the methods of historical-comparativ, discourse analysis and socio-communicative approach, the functions of the jadid press in the formation of national consciousness, the promotion of enlightenment reforms and political mobilization are determined. The results show that the Jadid press functioned not only as a reflection of Turkestan modernization, but as its communicative mechanism and intellectual infrastructure.